INCIDENCE AND DIVERSITY OF SOIL MYCOFLORA OF WARDHA (M.S) AREA: Life Science-Botany - L.P.DALAL (International Journal of Life Science and Pharma Research, 2012)
An experiment was conducted during the year 2011 to explore the different form of fungi. In present investigation and Rhizopus stolonifers Aspergillus, Penicillium. were found more prevalent in soil mycoflora of different areas of the city. A marked variation in soil mycoflora in different areas were also found in different seasons. Fungal species like Aspergillus sp. Penicillium and Rhizopus stolonifers were reported more prevalent in the seasons of 2011. Some fungi were more restricted and reported in particular environmental conditions like Rhizopus species, Pyricularia and Aureobasidium sp, Phoma sp., were restricted in particular months of a year. It was also reported that some fungal species were less prevalent like Curvularia lunata and Aureobasidium sp, and Helminthosporium sp. In Present investigation it was reported that fungal species like Aspergillus niger, Aspergillus flavus, Penicillium sp. were more prominent in all types of environment of soil of Wardha City (M.S.) and shown biodiversity in fungal soil mycoflora.